Rethinking the Three R's in Animal Research Replacement, Reduction, Refinement - Lauwereyns, Jan (Springer International Publishing, 2018)
This work challenges the current reliance on "The Three R's" or Replacement, Reduction and Refinement which direct most animal research in the behavioral sciences. The author argues that these principles that were developed in the 1950's to guide the use of animals in research studies are outdated. He suggests that the notions of refinement and reduction are often ill-defined and can be useful only in cases where replacement is impossible. .